Building a competitive First Nation investment climate - Tulo Centre of Indigenous Economics; BC Open Textbook Project; BCcampus (Tulo Centre of Indigenous Economics, 2014)
"This is the first edition of the open text book Building a Competitive Investment Climate on First Nation Lands. This textbook is for students who are First Nation and tribal government employees or students who would like to work for or with First Nation and tribal governments. The purpose of this textbook is to help interested First Nation and tribal governments build a competitive investment climate. Work began on this text book in early 2012 with a generous grant from the Donner Canadian Foundation. Financial support was also provided by the First Nations Tax Commission and the Tulo Centre."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Title from BC Campus Website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Indians of North America -- Canada; Investment of public funds -- Canada -- Textbooks; Electronic books